Pityriasis versicolor: clinical-epidemiological characterization of patients in the urban area of Buerarema-BA , Brazil Pitiríase versicolor: caracterização clínico-epidemiológica em pacientes da área urbana de Buerarema-BA, Brasil - Juliano Oliveira Santana; Fernanda Luiza Andrade de Azevedo; Pedro Costa Campos Filho (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Pityriasis versicolor (PV) is a cutaneous pigmentation disorder caused by a lipophilic yeast of the genus Malassezia sp. It is a superficial mycosis characterized by well-defined, slightly scaly skin lesions of variable color. In Brazil, the number of reported cases is small, and there are few epidemiological studies. OBJECTIVES: to assess incidence, characteristics of the lesions, effectiveness of the Zileri's Sign procedure, and the epidemiological profile of PV in the urban area of Buerarema - Bahia. METHODS: Biological samples were collected on pre-established days at Basic Health Care Units from July to September 2010. Sample collection was followed by laboratory diagnosis using Porto's Method. RESULTS: Of the 158 patients with suspected PV participating in the study, 105 (66.5%) were positive; 72 (68.6%) were female and 33 (31.4%) were male. Sex and location of lesions showed statistically significant differences (p<0.05). The region with the highest rate of cases of PV was found to be the center of the city, with 40.9% of diagnosed cases. The most affected age group was between 10 and 19 years. There was a significant association between the results produced through Zileri's Sign and Porto's Method in relation to positive and negative results (p<0.05). CONCLUSIONS: The results showed a higher prevalence of PV among individuals at puberty. The Zileri's Sign method proved to be counterproductive, because it showed low efficacy as a method for clinical diagnosis, yielding negative results for 36 (34.3%) patients who had been diagnosed with PV through laboratory examination. FUNDAMENTOS: A pitiríase versicolor é um distúrbio de pigmentação cutânea causada pela levedura lipofílica do gênero Malassezia sp. É uma micose superficial caracterizada por produzir lesões delimitadas, com descamação fina e de cor variável. No Brasil, o relato do número de casos e de estudos é restrito. OBJETIVOS: Analisar a incidência, as características das lesões, a eficácia do Sinal de Zileri e o perfil epidemiológico da pitiríase versicolor na área urbana do município de Buerarema-BA. MÉTODOS: Foram coletadas amostras biológicas no período de julho a setembro de 2010, em dias pré-establecidos, nas Unidades Básicas de Saúde. O Método de Porto foi utilizado como diagnóstico laboratorial. RESULTADOS: Dos 158 pacientes cadastrados com suspeita de pitiríase versicolor, 105 (66,5%) mostraram-se positivos, sendo 72 (68,6%) do sexo feminino e 33 (31,4%) do sexo oposto. Ocorreu diferença estatisticamente significante entre sexo e localização das lesões (p<0,05). A região com maior índice de pitiríase versicolor foi detectada no centro do município com 40,9% dos casos diagnosticados. A faixa etária mais acometida foi entre 10 e 19 anos. Houve associação significante entre o resultado do Sinal de Zileri e do Método de Porto em relação aos resultados positivos e negativos (p<0,05). CONCLUSÕES: Frente aos resultados, observou-se maior prevalência da pitiríase versicolor em jovens no período da puberdade. O Sinal de Zileri mostrou-se contraproducente, pois não demonstrou eficácia como método de diagnóstico clínico ao gerar resultados negativos em 36 (34,3%) pacientes, cujas amostras ostentaram positividade no exame laboratorial.